Diabetes in patients after kidney transplant - Polski, Paweł; Alzubedi, Adam; Kusz, Monika (Journal of Education, Health and Sport, 2018)
Diabetes is a group of metabolic diseases characterized by hyperglycaemia associated with inadequate insulin secretion or poor cells response to insulin. It can affect a large proportion of patients after a kidney transplant. New onset diabetes after transplantation (NODAT) is often associated with the use of immunosuppressive drugs including steroids. However, a significantly greater number of risk factors affect the development of the disease. The occurrence of diabetes after renal transplantation is associated with some limitations in society function and significantly impairs the proper conduct of such patients in outpatient departments. Frequent drug modifications may result in much faster impairment of the grafted kidney function and eventually loss of graft. This work aims to show the essence of the disease, to assess the risk factors of its development, and to show the role of diabetes education to help patient affected by the disease.